2018
DOI: 10.1093/cvr/cvy067
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of endothelial progenitor cell-derived extracellular vesicles from shear-thinning hydrogels improves angiogenesis and promotes function after myocardial infarction

Abstract: EPC-derived EVs delivered into ischaemic myocardium via an injectable hydrogel enhanced peri-infarct angiogenesis and myocardial haemodynamics in a rat model of MI. The STG greatly increased therapeutic efficiency and efficacy of EV-mediated myocardial preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 47 publications
1
125
0
Order By: Relevance
“…For applications such as bone tissue where much higher moduli are required, dECM bioinks can be combined with 3D printed porous PCL scaffolds, which can reach compressive moduli in the MPa range . In addition, there have also been efforts to develop shear‐thinning hydrogels that can flow through the needle and retain their shape after they have been printed . Such approaches may be translated into the printing of dECM to improve its printability.…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For applications such as bone tissue where much higher moduli are required, dECM bioinks can be combined with 3D printed porous PCL scaffolds, which can reach compressive moduli in the MPa range . In addition, there have also been efforts to develop shear‐thinning hydrogels that can flow through the needle and retain their shape after they have been printed . Such approaches may be translated into the printing of dECM to improve its printability.…”
Section: Postdecellularization Processing Methodsmentioning
confidence: 99%
“…107 In addition, there have also been efforts to develop shear-thinning hydrogels that can flow through the needle and retain their shape after they have been printed. [108][109][110] Such approaches may be translated into the printing of dECM to improve its printability.…”
Section: Bioinkmentioning
confidence: 99%
“…Indeed, stimulation of cardiomyocytes undergoing Angiotensin II-induced hypertrophy and apoptosis with EPC-derived microvesicles resulted in improved survival as mediated by RNA-driven modulation of PI3K/Akt/eNOS pathway [177]. More recently, EPC-EVs have been administered to a rat model of MI within a shear-thinning hydrogel for their precise delivery and steady release, thus sustaining cardiac function and enhancing vessel density [178]. Notably, interleukin-10 deficiency within EPC-EVs has been recently shown to significantly affect their therapeutic influence for myocardial repair as altering their protein cargo and upregulating integrin-linked kinase-mediated activation of NF-κB in recipient cells; thus, modulation of the inflammatory priming of secreting EPC can impact on their EV profile and cardiovascular paracrine potential [179].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Many studies have concluded that the therapeutic effects of MSCs were mainly achieved through paracrine effects and the expression of proangiogenic cytokines after transplantation. Chen et al [32] found that endothelial progenitor cell-derived extracellular vesicles injected into ischemic myocardium through injection of hydrogel could enhance the angiogenesis and myocardial hemodynamics in the infarcted rat model. Angiogenic growth factor VEGF is thought to activate every step of proangiogenic endothelial cell behavior, such as endothelial cell invasion, migration, and attachment [33].…”
Section: Discussionmentioning
confidence: 99%